Studi Literatur: Agen Antivirus pada Pasien COVID-19 dengan Penyakit Ginjal Kronis - Meiliana, Made Laksmi; Hasmono, Didik (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2021)
At the end of 2019, Wuhan, Hubei Province, reported the first case of a virus similar to pneumonia. The World Health Organization (WHO) reports this outbreak as the Corona virus (COVID-19). Infection with COVID-19 may be more common in people who have chronic kidney disease (CKD). Patients with chronic kidney failure may experience infectious complications due to a weakened immune system and immunosuppressive state. Similarly, they suffer from a chronic systemic inflammatory state, which can contribute to increased morbidity and mortality. Thus, the purpose of this study is to conduct a review of antiviral agents and to summarize recommended antiviral regimens in COVID-19 patients with chronic kidney disease. This article search used Mendeley, Google Scholar, ScienceDirect, and PubMed from the NCBI database in October 2020. The administration of drugs to patients with chronic kidney disease who have been exposed to COVID-19 must be seriously considered. Certain antivirals must be adjusted to avoid deteriorating the patient's kidney condition. Antiviral agents are medications used to treat and prevent COVID-19 infection. Numerous antiviral agents, including ramdesivir, ribavirin, hydroxychloroquine or chloroquine, and umifenovir, must be administered with caution and dose adjustments as necessary in CKD patients exposed to COVID-19.